Critical Thinking in the Teaching of EFL Academic Writing - Imaniar, Fahmy; Pratama, Raga; Lestari, Lies; Munir, Ahmad (Institut Agama Islam Negeri Palopo, 2024)
This study aims at describing critical thinking subskills taught by Indonesian EFL teachers in academic writing and explaining how they taught the subskills. This qualitative study used two Indonesian EFL teachers who taught academic writing at one of state universities in Surabaya. Data were collected using observation checklist and field note. The obtained data were analyzed using interactive model analysis. Results showed that there were three out of forty critical thinking subskills that were not taught by the teachers namely providing and selecting the best examples, using credible sources, and maintaining the consistency of tenses choice. Another finding showed that there were seven ways of teaching critical thinking subskills namely individual consultation and feedback, class explanation, peer-feedback, groupwork of ideas construction and discussion, general class feedback, analysis task, and work review and discussion. This study suggests that EFL teachers can use the forty critical thinking subskills in teaching writing through one of the seven ways of teaching found.